Advanced Charting Techniques of Microsoft Excel 2016 Aiming Visualization - Mahajan, Kirti Nilesh; Gokhale, Leena Ajay (International Journal of Computer Sciences and Engineering, 2019)
Environment of Microsoft Excel integrates storage, analysis and visualization of data. After the data is stored in a precise structured format, further analysis and visualization of data is essential to discover the hidden valuable insight from the large dataset. Visualization supports extracting and understanding the information as it is represented in a graphical format. Visualization plays a vital role in decision making at various levels in the organization. There are numerous techniques of visualization. However, the most extensively used technique is to present the data in a chart format. Various charting techniques such as Column Chart, Pie Chart, Line Chart and Bar Chart are existing in Microsoft Excel application. In addition to these conventional charts, Microsoft Excel 2016 presents six advanced chart types named, Box and Whisker chart, Funnel chart, Histogram chart, Sunburst chart, Treemap chart and Waterfall chart to present the data differently. This paper describes illustrations of new chart types of Microsoft Excel 2016 along with their elements and respective attributes. The purpose of this research paper is to present how advanced charting techniques can be used for visualizing varied data types in the engineering manufacturing industries.